Systematic Review of Efficacy and Safety of Newer Antidiabetic Drugs Approved from 2013 to 2017 in Controlling HbA1c in Diabetes Patients - Sivanandy Palanisamy; Emily Lau Hie Yien; Ling Wen Shi; Low Yi Si; See Hui Qi; Laura Soon Cheau Ling; Teng Wai Lun; Yap Nee Chen (MDPI AG, 2018)
Type 2 Diabetes Mellitus (T2DM) is the most common form of diabetes mellitus and accounts for about 95% of all diabetes cases. Many newer oral as well as parenteral antidiabetic drugs have been introduced in to the market in recent years to control hyperglycemic conditions in diabetes patients and many of these drugs produce potential side effects in diabetes patients. Hence, this systematic review was aimed to analyze and compare the efficacy and safety of oral antidiabetic agents in controlling HbA1c in T2DM patients, that were approved by the United States-Food and Drug Administration (US-FDA) from 2013 to 2017. All randomized controlled, double-blind trials published in English during the search period involving the newer antidiabetic agents were selected. In the outcome assessment comparison, semaglutide demonstrated the highest efficacy in lowering HbA1c, with a 1.6% reduction (p < 0.0001) when given at a dose of 1.0 mg. The safety profile of all the agents as compared to placebo or control were similar, with no or slight increase in the occurrence of adverse events (AEs) but no fatal reaction was reported. The most common AEs of all the antidiabetic agents were gastrointestinal in nature, with several cases of hypoglycemic events. However, among all these agents, semaglutide seems to be the most efficacious drug to improve glycemic control in terms of HbA1c. Alogliptin has the least overall frequency of AEs compared to other treatment groups.